The Bell Telephone Historical Collection and Late Nineteenth-Century Canadian Urban History: A Preliminary Report - Norris, Darrell (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1982)
In 1878, the first telephone exchange in the British Empire was put into service at Hamilton, Ontario. By 1891, the Bell Telephone Company of Canada had completed a long-distance network exceeding 6400 kilometres, including an unbroken link along Central Canada's "Main Street," between Quebec City and Windsor. The company's operations in 1891 embraced 22,000 subscribers and more than 200 exchanges.The spread of the long-distance network was halting at first, owing to the meagre capital resources of the company and the relatively poor return on investment given just a few thousand subscribers in the entire system. Also, much of the initial capital investment was quickly rendered obsolete, because of technical improvements in voice transmission over copper metallic circuits, which by the mid-1880s had begun to replace and augment existing long-distance links by iron wire.This research note discusses the development of the long-distance telephone network in Central Canada, its evolving pattern of telephone exchanges, the spread of telephone adoption, and the intensity with which the long-distance system was used in its formative phase. The research was completed under the auspices of the Historical Atlas of Canada/Atlas Historique du Canada.